Penjatuhan Sanksi Hukum Bagi Masyarakat Yang Menyalahgunakan Fungsi Trotoar Di Kecamatan Abiansemal - I Putu Eka Dipratama; Gede Made Swardhana (Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of making a research journal is to find out the forms of sanctions given to people who abuse the function of sidewalks and to find out the concrete steps taken by the Abiansemal sub-district head and security forces in organizing people's lives, especially in controlling the function of sidewalks. This research uses empirical legal research methods. Notification regarding the general public is one of the concurrent government affairs between the Central Government and the Provincial and Regency/City Regional Governments. Public order and public peace are manifestations of human rights in an orderly society, national and state life. Sidewalks are one of the many important facilities to complement the development of all activities on an environmental scale, but the clear function of sidewalks does not rule out the possibility of covering many functions of these sidewalks. The cause of violations of the function of sidewalks is due to gaps or lack of understanding of people who want to sell on sidewalks or use parking spaces, which results in many things or cases related to sidewalks.